Beneficial Effects of Musicality on the Development of Productive Phonology Skills in Second Language Acquisition - Delogu, Franco; Zheng, Yi (Frontiers in Neuroscience, 2020)
Previous studies show beneficial effects of musicality on the acquisition of a second language (L2). While most research focused on perceptual aspects, only few studies investigated the effects of musicality on productive phonology. The present study tested if musicality can predict productive phonological skills in L2 acquisition. 63 students with no previous exposure to Arabic were asked to repeatedly listen to and immediately reproduce short sentences in standard Arabic. Before the sentence reproduction task, they completed an auditory discrimination task in three different between-subjects condition: attentive, in which participants were asked to discriminate phonological variations in the same Arabic sentence that they were asked to reproduce later; non-attentive, in which participants were asked to detect beeps in the same Arabic sentences without paying attention to their phonological content; and no-exposure, in which participants performed the discrimination task in another language (Serbian). The first, third and seventh reproductions of each participant were rated for intelligibility, accent and syllabic errors by two independent evaluators, both native speakers of Arabic. Primary results showed that the intelligibility of the reproduced sentences was higher in participants with high-musicality scores in the Advanced Measures of Music Audiation (AMMA). Moreover, the intelligibility of sentences produced by highly musical participants improved more over time than the intelligibility of participants with lower musicality scores. Previous exposure to the Arabic sentence was beneficial in both the attentive and non-attentive conditions. Our results support the idea that musicality can have effects on productive skills even in the very first stages of L2 acquisition.